Risk of variant Creutzfeldt–Jakob disease transmission by blood transfusion in Australia. Issue 8 (24th May 2022) - McManus, Hamish; Seed, Clive R.; Hoad, Veronica C.; Kiely, Philip; Kaldor, John M.; Styles, Claire E.; Yang, Hong; Law, Matthew; Gosbell, Iain B.
Abstract: Background and Objectives: Most of the 233 worldwide cases of variant Creutzfeldt–Jakob disease (vCJD) have been reported in the United Kingdom and 3 have been associated with transfusion‐transmission. To mitigate the potential vCJD risk to blood safety, Australian Red Cross Lifeblood imposes restrictions on blood donation from people with prior residency in, or extended travel to, the United Kingdom during the risk period 1980–1996. We have modified a previously published methodology to estimate the transfusion‐transmission risk of vCJD associated with fresh component transfusion in Australia if the UK residence deferral was removed. Materials and Methods: The prevalence of current pre‐symptomatic vCJD infection in the United Kingdom by age at infection and genotype was estimated based on risk of exposure to the bovine spongiform encephalopathy agent for the period 1980–1996. These results were used to estimate the age‐specific prevalence of undiagnosed, pre‐symptomatic vCJD in the Australian population in the current year due to prior UK residency or travel. The primary model outputs were the 2020 vCJD risks/unit of vCJD contamination, transfusion‐transmission (infections) and clinical cases. Results: The overall (prior UK residency in and travel to United Kingdom, 1980–1996) mean risk of contamination per unit was 1 in 29, 900, 000. The risks of resulting vCJD transmission (infection) and clinical case were 1 in 389, 000, 000 and 1 in 1, 450, 000, 000, respectively. Conclusion: Our modelling suggests that removing the Lifeblood donation deferral for travel to, or UK residence, would result in virtually no increased risk of vCJD transfusion‐transmission and would be a safe and effective strategy for increasing the donor base.